Studi Segmentation, Targeting, Positioning (STP) pada Bauran Pemasaran Produk Klinik Eksekutif Rumah Sakit Gigi Mulut pada Masa Pandemi COVID-19 - Meutia Arini Yasrizal; Wahyu Sulistiadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze segmentation, target market and market position in the product marketing mix of the executive clinic of the Oral Dental Hospital (RSGM) X Jakarta City. The method used is descriptive quantitative. The results showed that in the segmentation analysis, most visits to the clinic were women of productive age, predominantly from outside the DKI Jakarta area, dominant payments were out of pocket and insurance, and the dominant type of service used was executive service. Targeting analysis shows that the best market determination strategy for RSGM X is multi-targeting. Strengthening positioning at RSGM X can be done by prioritizing superior products, brand attributes and the quality of services provided. In conclusion, RSGM X prioritizes services with adjustments to health protocols through marketing strategies with segmentation, target and position concepts and is supported by the right marketing mix. Keywords: Market Position, Segmentation, Target Market